(untitled) (Research, Society and Development, 2022)
The theme of School Inclusion has been present in several discussions about education in recent decades, gaining more focus, in Brazil, from the National Policy on Special Education in the Perspective of Inclusive Education (PNEEPEI) of 2008. The guiding documents mention that Special Education and Common Teaching must work in an articulated way, but it does not define when and how this work should happen. In this way, the general objective of this study is to analyze desires and impediments that manifest the teachers of the municipal network of Nova Prata-RS for the promotion of articulated actions between common classroom and Specialized Educational Assistance (SEA). This exploratory research with a qualitative approach adopted the semi-structured interview as data collection technique and was carried out with teachers of SEA and the final years of Elementary School from two urban municipal schools whose reports were analyzed in the light of theoretical studies related to the theme. In the findings, it was evidenced that the SEA is perceived as a support to the regular education teacher and the Special Education student, but there are complaints about the distance and isolation between professionals. The research participants express the need for a planned and organized time to articulate more effective strategies, alerting to the need for legal guarantees with forecast and provision of the necessary resources so that the articulation between Special Education and the final years of Elementary School happens in a more effective way.